Analysis of Judges' Considerations In Implementing Sanctions for Criminal Acts of Planning Murder (Case Study of Decision No. 632/Pid.B/2021/Pn.Ckr) - Zahrah Nur Kamilah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
One of the uncivilized cases that occurs in the community is a murder case, which is the act of killing another person's life either immediately at that time or with a plan in advance. Examples of premeditated murder cases that have occurred are in Court Decision No. 632/Pid.B/2021/PN.Ckr. In this case, the writer wants to know how to regulate criminal sanctions against perpetrators of premeditated murder and how judges consider in imposing sanctions against criminals in Decision Number 632/Pid.B/2021/PN.Ckr. The judge's consideration in the Cikarang District Court Decision 632/Pid.B/2021/PN.Ckr, is based on juridical considerations, namely the legal facts revealed at trial in the form of statements from witnesses, evidence and evidence as well as the defendant's own statement, then related to the article that was charged to the defendant, namely Pasal 340 KUHP as stated in the first alternative indictment of the Public Prosecutor's indictment, and as the result of the evidence of the elements in Pasal 340 KUHP, the defendant was declared legally and convincingly guilty of committing a crime of premeditated murder, so that in According to its decision, the Assembly sentenced the defendant to 20 (twenty) years in prison. The sentence is also based on non-juridical considerations, namely things that are aggravating and mitigating the defendant.